First factor (x square -36), the answer will be (x+6)(x-6).
Second, cancel the x .
6x/ (x+6)(x-6)
4x/(6)(-6)
4x/-36
Hey there! I'm happy to help!
A proportional equation follows the form y=kx, where k is the constant of proportionality.
Answer 1 is wrong because there is something added.
2 is correct as it follows this format.
3 is incorrect as it does not follow this format.
4 is correct as it follows the format (k is 1)
5 Is correct because it follows this format.
6 is not correct because there is a 1 added, which does not follow the format.
Therefore, the correct answers are 2, 4, and 5.
Have a wonderful day! :D
Answer:
14
Step-by-step explanation:
In a triangle, the midline joining the midpoints of two sides is parallel to the third side and half as long, so
FB = EC/2
2x - 6 = 44/2
2x - 6 = 22
2x = 22 + 6
2x = 28
x = 28/2
x = 14
Answer:
6=65
Step-by-step explanation:
34
Answer:
32
Step-by-step explanation:
(4x6)/2+(2x2)/2+2x2+(2x6)/2